2013
DOI: 10.1083/jcb.201208163
|View full text |Cite
|
Sign up to set email alerts
|

Pericentric chromatin loops function as a nonlinear spring in mitotic force balance

Abstract: During mitosis, cohesin- and condensin-based pericentric chromatin loops function as a spring network to balance spindle microtubule force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 77 publications
(132 reference statements)
1
97
0
Order By: Relevance
“…8D). Importantly, it has been shown that chromosomes can act like springs to counteract the motive force of the mitotic spindle, which would also support this model (60). Because separated SPBs also collapse back together in some nimA7 cells, this suggests that some connection is maintained between the segregated kinetochores and the separated SPBs before kinetochores are pulled back together via unresolved sister chromatids (Fig.…”
Section: Initiation Of Mitosis In the Absence Of Sufficient Nima Funcmentioning
confidence: 72%
“…8D). Importantly, it has been shown that chromosomes can act like springs to counteract the motive force of the mitotic spindle, which would also support this model (60). Because separated SPBs also collapse back together in some nimA7 cells, this suggests that some connection is maintained between the segregated kinetochores and the separated SPBs before kinetochores are pulled back together via unresolved sister chromatids (Fig.…”
Section: Initiation Of Mitosis In the Absence Of Sufficient Nima Funcmentioning
confidence: 72%
“…At least one function of pericentric cohesion is to facilitate kinetochore biorientation by resisting the pulling forces of microtubules and/or by promoting the architecture of sister kinetochores (Eckert et al 2007;Fernius and Marston 2009;Ng et al 2009;Bloom and Joglekar 2010). Consistent with this, the geometry and elasticity of the pericentromere and inner kinetochore can change in response to alterations in microtubule dynamics (Haase et al 2012;Stephens et al 2013). These properties are regulated by the Bub1 and Sgo1 proteins as well as various chromatin-remodeling complexes (Haase et al 2012;Verdaasdonk et al 2012).…”
Section: The Centromerementioning
confidence: 92%
“…Although force-balance ideas had previously been proposed to explain metaphase chromosome positioning (9, 10), Saunders and Hoyt's work appears to be the first force-balance model of the spindle structure. The force-balance picture was supported by further work in yeasts showing that kinesin-14s can counteract kinesin5s (11,12) and since then has been both widely adopted as a conceptual framework (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and used in mathematical models (23)(24)(25)(26)(27) of yeast spindles. Quantitative force-balance models were later applied to Drosophila spindle assembly (28)(29)(30)(31), and the same ideas have more recently been extended to human cells (32).…”
Section: Introductionmentioning
confidence: 97%